A study of the graduates of health economics masters programs in Spain - Manuel Ruiz-Adame Reina; Manuel Correa; Nuria García-Agua Soler (Elsevier, 2019)
Objective: To identify the characteristics, motivations and employment implications among graduates of Masters programmes in health-economics (MPHE). Method: The most renowned MPHE in Spain were contacted to assist in this research study. Participants submitted an online survey comprising 30 items designed specifically for the purpose. Our sample consisted of 439 graduates. Different statistical analysis, including a logistic model, were performed to describe the sample. Results: The main motivation for undertaking an MPHE is academic, and to acquire new or enhance previous knowledge. The general profile of graduates is that of a woman aged 37.8 and a health professional. Those looking for a job in Health Economics generally found employment in the first (54.9%) or second year (29.7%). MPHE were very highly assessed. The most useful subject was health management (46.3%). Conclusions: Undertaking an MPHE is a good investment because most of the graduates believed that their training enabled them to find a job. The graduates showed a high degree of confidence in the usefulness of the training. MPHE are highly evaluated irrespective of consequent employment. The subjects in which the curriculum vitae of the health professionals were weaker, such as those concerning management, were evaluated the highest as they were assumed to enhance promotion opportunities. Resumen: Objetivo: Identificar las características, las motivaciones y las implicaciones laborales que aparecen entre los egresados de programas de máster en economía de la salud (PMES). Método: Se solicitó colaboración a los másteres más relevantes de España para esta investigación. Los participantes completaron un cuestionario on line de 30 ítems específicamente diseñado para este propósito. La muestra estuvo formada por 439 egresados. Se realizaron diferentes análisis estadísticos, incluyendo modelos logísticos. Resultados: La principal motivación para hacer un PMES es la académica. Las personas lo hacen con el fin de adquirir nueva formación o mejorar conocimientos previos. El perfil general de egresado es el de una mujer de 37,8 años, profesional sanitaria. Las personas que buscaban trabajo en economía de la salud lo encontraron principalmente en el primer (54,9%) o segundo (29,7%) año. La valoración de los PMES es muy elevada. La materia más útil fue gestión sanitaria (46,3%). Conclusiones: Hacer un PMES es una buena inversión porque la mayoría de los egresados consideran que obtuvieron un empleo gracias a su formación. Los graduados muestran un alto grado de confianza en la utilidad de la formación. Los PMES son altamente valorados independientemente de las consecuencias laborales. Las materias en las que los curricula vitae de los sanitarios son más débiles, como las relativas a gestión, son las mejor valoradas, ya que suponen mejores oportunidades de promoción. Keywords: Graduates, Masters programmes, Health economics, Human capital, Job, Spain, Palabras clave: Egresados, Programas de máster, Economía de la salud, Capital humano, Empleo, España